Closing the knowledge gap with narrative visualizations: lessons from a research-practice partnership promoting multilingual students' academic success - Siebert, Julian M. (Frontiers in Education, 2025)
This paper addresses the use of narrative visualizations as an effective way to improve communication, engagement, and knowledge transfer in research-practice partnerships (RPPs). I report on the experience of developing a narrative visualization reporting research findings to educators/school leaders in an RPP focused on providing more equitable access to high school mathematics courses for multilingual students [referred to as English learners (ELs) in the US]. The narrative visualization was intended to allow easy interpretation of information on: (i) student rates of completion of courses that are critical to becoming eligible for college admission; (ii) student mathematics course trajectories; and (iii) mathematics course placement decisions. Using the notion of graphical excellence, I identify specific visualization strategies and features that improve the quality of the narrative visualization and support practitioners use of them. Drawing on liberatory design thinking, I discuss how this form of reporting findings builds trust and facilitates engagement between partners, increases practitioners' agency, and thus creates more equitable power dynamics in RPPs and for the multilingual students at the core of the one discussed here.